Epstein‐Barr virus LMP2A utilizes Syk and PI3K to activate NF‐κB in B‐cell lymphomas to increase MIP‐1α production. Issue 5 (4th January 2019) - Incrocci, Ryan; McAloon, Jason; Montesano, Michael; Bardahl, Jonathan; Vagvala, Saivenkat; Stone, Amanda; Swanson‐Mungerson, Michelle
Abstract : The incidence of Hodgkin's lymphoma (HL) is growing due to an increase in Epstein‐Barr virus (EBV)‐associated HL in AIDS patients. The HL tumor microenvironment is vital for the survival of the malignant Hodgkin‐Reed Sternberg (HRS) cells of HL, which express the EBV protein latent membrane protein 2A (LMP2A). While previous work shows that LMP2A mimics B‐cell receptor (BCR) signaling to promote the survival of HRS cells, the ability of LMP2A to establish and maintain the tumor microenvironment through the production of chemokines remains unknown. Since BCR signaling induces the production of the chemokine macrophage inflammatory protein‐1α (MIP‐1α), and since LMP2A is a BCR mimic, we hypothesized that LMP2A increases MIP‐1α levels. A comparison of multiple LMP2A‐negative and ‐positive cell lines demonstrates that LMP2A increases MIP‐1α. Additionally, LMP2A‐mutant cell lines and pharmacologic inhibitors indicate that LMP2A activates a Syk/PI3K/NF‐κB pathway to enhance MIP‐1α. Finally, based on the finding that an NF‐κB inhibitor decreased MIP‐1α RNA/protein in LMP2A‐positive cells, we are the first to demonstrate that LMP2A increases the nuclear localization of the NF‐κB p65 subunit using DNA‐binding assays and confocal microscopy in human B cells. These findings not only have implications for the treatment of HL, but also other LMP2A‐expressing B‐cell tumors that overexpress NF‐κB.